Utilizing the Quranic Corpus to Enhance Arabic Language Learning: Opportunities and Challenges - Yusuf, Kamal (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The Quranic Arabic Corpus is a rich linguistic resource, offering morphological, syntactic, and semantic analysis for every word in the Quran. Developed by the University of Leeds, this corpus facilitates an in-depth understanding of the sentence structure and vocabulary of classical Arabic. Utilizing this corpus in Arabic language learning can improve linguistic analysis skills, deepen grammatical understanding, and enrich appreciation of the beauty of the Quranic language. However, despite its great potential, the application of this corpus in Arabic language teaching is still limited. This study aims to explore the benefits of the Quranic Corpus in enhancing Arabic language teaching, as well as identify the challenges and opportunities this technology presents in Arabic language education in educational institutions.